Decomposing Employment Trends of Disabled Workers - Pierre Koning; Heike Vethaak (Tinbergen Institute, 2019)
Many OECD countries are facing decreases in the employment rates of disabled workers. To uncover the driving forces of these trends, this paper estimates Age-Period-Cohort (APC) models on administrative data of Disability Insurance (DI) application cohorts for the Netherlands between 1999 and 2013. Our main finding is that the substantial decrease in employment rates of applicant cohorts in this time period is almost fully explained by cohort effects - equalling about 30 percentage points - and that the impact of period effects is only small. In turn, cohort effects stem from changes in the observed composition of applicants, with increasing shares of workers without (permanent) contracts in the year before the application. These changes are largely confined to years following two major DI reforms that increased self-screening among potential applicants. We also expand the APC model by allowing for distinct effects for awarded and rejected DI applicants. Assuming common compositional cohort effects for these two groups, difference-in-difference estimates of cohort effects indicate that the effect of changes in benefit conditions ('incentive effects') is limited. Disability reforms thus predominantly affected the stringency of the DI system and induced substantial self-screening in the sickness period before the DI decision, rather than changing individual employment rates.
Keywords: H75; J21; C23; 330; Disability Insurance; employment; age-period-cohort model